2017
DOI: 10.1080/09638288.2017.1300950
|View full text |Cite
|
Sign up to set email alerts
|

Physical symptoms and working performance in female breast cancer survivors: a systematic review

Abstract: These symptoms and physical limitations led to the difficulty or impossibility of performing work tasks, which also diminished work productivity, as well as the increase in time to return to work. The present results suggest higher unemployment rates and the need for modifying work conditions. Implication for Rehabilitation Health professionals should include risk assessment at daily routine to identify possible sources of physical impairments for upper limbs. Provide the support and orientations according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 28 publications
2
49
0
1
Order By: Relevance
“…In the present study, there were significantly more survivors with the SC who worked part-time or who were on sick leave or disabled than those without the SC. Cancer-related symptoms such as pain, fatigue, and psychological distress have been associated with unemployment in several studies, but all these studies have investigated one symptom at a time [23][24][25]. To our current knowledge, the present study is the first to show that the SC of pain, fatigue, and psychological distress after breast cancer treatment is associated with reduced ability to work for many years after the diagnosis.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 59%
See 1 more Smart Citation
“…In the present study, there were significantly more survivors with the SC who worked part-time or who were on sick leave or disabled than those without the SC. Cancer-related symptoms such as pain, fatigue, and psychological distress have been associated with unemployment in several studies, but all these studies have investigated one symptom at a time [23][24][25]. To our current knowledge, the present study is the first to show that the SC of pain, fatigue, and psychological distress after breast cancer treatment is associated with reduced ability to work for many years after the diagnosis.…”
Section: Sociodemographic Characteristicsmentioning
confidence: 59%
“…Getting patients back to work is one of the first and most important goals after treatment is completed. However, several studies have shown that breast cancer survivors have an increased risk of unemployment [21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review demonstrated that breast pain and weakness in the arms are the most common physical side effects of surgical treatment for breast cancer; these side effects can affect working performance in breast cancer survivors (Zomkowski et al, 2018).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Persistent or chronic pain due to surgical treatment is common among patients with breast cancer; such pain continues for 6 months in 6%–33% of patients and for 3–6 years in 16%–70% of patients (Andersen & Kehlet, ; Mak et al, ). A systemic review demonstrated that breast pain and weakness in the arms are the most common physical side effects of surgical treatment for breast cancer; these side effects can affect working performance in breast cancer survivors (Zomkowski et al, ). Fatigue—a subjective sense of tiredness, weakness, exhaustion and enervation—is another common side effect that persistently affects patients with breast cancer (Hofman, Ryan, Figueroa‐Moseley, Jean‐Pierre, & Morrow, ; Kinkead et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, tertiary prevention in those workers with clinical outcomes, also with the help of physiotherapists, psychologists and occupational therapists [18,19,38,48,49].…”
mentioning
confidence: 99%